2003
DOI: 10.1373/49.1.167
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Androstenedione Ingestion on Plasma Testosterone in Young Women; a Dietary Supplement with Potential Health Risks

Abstract: Androstenedione is readily available as a "dietary supplement" and can be sold without restriction in most countries, including the US and UK. Manufacturers market androstenedione as a "prohormone" that can increase blood testosterone concentration, thereby increasing lean body mass and strength. It is available in capsules purported to contain 50, 100, or 300 mg of the steroid, and the manufacturers suggest that the "desired" effects can be gained by taking 100 -300 mg/day orally. However, a single dose of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 14 publications
3
11
0
Order By: Relevance
“…40 The mean exposure (as determined by area under the curve) to testosterone was greater than an order of magnitude compared to the control period, and the plasma concentrations observed were similar to those encountered in abuse of T for anabolic purposes. A similar pro¢le would be expected with chronic administration, but the risk of virilization precludes such a study.…”
mentioning
confidence: 62%
“…40 The mean exposure (as determined by area under the curve) to testosterone was greater than an order of magnitude compared to the control period, and the plasma concentrations observed were similar to those encountered in abuse of T for anabolic purposes. A similar pro¢le would be expected with chronic administration, but the risk of virilization precludes such a study.…”
mentioning
confidence: 62%
“…Effects of ADION administration on male and female volunteers has been thoroughly investigated in the past, and especially in males, effects were found less pronounced compared to T administrations. [22][23][24] One interesting point in the context of sports drug testing may be the fact that ADION is not only converted to T but also to E and therefore administrations result in less elevated T/E ratios. [25] Therefore, ETIO and A concentrations were considered as promising candidates to detect ADION administrations together with different 6-hydroxylated metabolites.…”
Section: Androstenedionementioning
confidence: 99%
“…Recently, two studies evaluated the serum testosterone response to androstenedione intake in women. Kicman et al [12] administered 100 mg androstenedione to young (20 ± 32 y) women and observed an~25 nmol/l increase in serum total testosterone. In contrast, Leder et al [13] administered 50 mg and 100 mg androstenedione to older (47 ± 64 y) women and observed that serum testosterone concentrations were increased by~2.1 nmol/l and 3.5 nmol/l, respectively.…”
Section: Introductionmentioning
confidence: 99%